Full-Duplex DF Relaying With Parallel Hybrid FSO/RF Transmissions - Michalis P. Ninos (IEEE, 2021)
The ever-increasing demands for higher data rates in telecommunications networks, along with the significant benefits offered by wireless communications, have pushed the technological developments to new frontiers. Free-space optical (FSO) communications are among the technologies that can address these emerging demands, offering large and unregulated bandwidth. In addition, recent advances in radio frequency (RF) systems have enabled the development of in-band full-duplex (FD) radios with the employment of advanced self-interference cancelation techniques. Therefore, in this paper we study a robust FD relaying system comprised of parallel hybrid FSO/RF communication links, where the coordination of transmissions between the FSO/RF subsystems is carried out by the hard-switching protocol. The operation of the RF links is impaired by Nakagami- $m$ fading, the residual self-interference due to the FD relaying operation, and the in-phase and quadrature-phase imbalance effect due to imperfect RF front-ends. As far as the FSO links are concerned, we consider the influence of the joint effects of atmospheric turbulence, beam wander and pointing errors. We first derive analytical closed-form expressions for the outage probability of both subsystems as well as for the overall FD relaying hybrid system. Then, asymptotic expressions are extracted for the outage performance in the high signal-to-noise ratio regime. The achievable outage diversity orders of both FSO and RF subsystems are determined, which provide significant insight into the design of such hybrid systems in a wide variety of operating conditions. Finally, the numerical results are presented using the derived outcomes, and significant conclusions are drawn about FD relaying hybrid systems.